Age of First Suicide Attempt in Men and Women: An Admixture Analysis - Hilario Blasco-Fontecilla; Analucia A. Alegria; David Delgado-Gomez; Teresa Legido-Gil; Jeronimo Saiz-Ruiz; Maria A. Oquendo; Enrique Baca-Garcia (The Scientific World Journal)
Objectives. To define different subgroups of suicide attempters according to age at onset of suicide attempts. Methods. Participants were 229 suicide attempters (147 females; 82 males) admitted to a general hospital in Madrid, Spain. We used admixture analysis to determine the best-fitting model for the age at onset of suicide attempts separated by sex. Results. The best fitted model for the age at onset of suicide attempts was a mixture of two gaussian distributions. Females showed an earlier age at onset of suicide attempts in both Gaussian distributions (mean ± S.D.) (26.98 ± 5.69 and 47.98 ± 14.13) than males (32.77 ± 8.11 and 61.31 ± 14.61). Early-onset female attempters were more likely to show borderline personality disorder than late-onset female attempters (OR = 11.11; 95% CI = 2.43–50.0). Conclusions. Age at onset of suicide attempts characterizes different subpopulations of suicide attempters.